Capital Market Effects of U.S.-Canada GAAP Differences - Bandyopadhyay, Sati P.; Hanna, J. Douglas; Richardson, Gordon (Journal of Accounting Research, 1994)
Canadian firms that list securities on U.S. stock exchanges are generally required to provide a reconciliation of reported income measured using Canadian generally accepted accounting principles (GAAP) to reported earnings measured using U.S. GAAP. This paper examines both the magnitudes and the information content of the reported reconciliations between CanadianGAAP income and U.S.GAAP income. Two recent studies of cross-country GAAP differences do not address U.S.-Canada differences because of perceived similarities between GAAP in the two countries (Amir, Harris, and Venuti [1993] and McQueen [1993]). If U.S.-Canada GAAP differences are in fact unimportant, then no further examination is warranted. Professional bodies, however, are